THE INTERESTING ADVENTURE OF MIGRATED REINFORCEMENT SUTURE IN A SLEEVE GASTRECTOMY PATIENT - Aktimur, R.; Kirkil, C. (Springer, 2016)
[Abstract Not Available]
21st World Congress of International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO) -- SEP 28-OCT 01, 2016 -- Rio de Janeiro, BRAZIL
Keywords: reinforcement suture; migration; sleeve gastrectomy